Universalism v cultural relativism of international law: Legality of whaling - Nur Amani, Pauzai; Farhanin, Abdullah Asuhaimi; Khairun-Nisaa, Asari; Maheran, Makhtar (2018)
Universalism and cultural relativism in international has been debated by the scholar for decades. The supporter of the universalism hold that human rights are universal in nature and shall apply to every human being. Whereas, from the cultural relativists opinion that the law or the moral principles are dependent on culture, so no law or moral can be made to apply to all cultures. With regard to the legality of whaling, the whale hunting has been practiced by the thousands of years ago for meat, bones and oil. As for today there is a few countries which still practice the whaling as part of their culture like Japan, Iceland, Faroe Island and Norway. The question is how far the cultural relativism legalise the killing of endangered species; and can the nongovernmental organisation take action, by their own hand, in suppressing the whaling. This paper will look in the matter using traditional research method that mainly based on the library search. The data will be gathered from the legal documents such as international conventions, statutes, reported cases, legal journals, articles and relevant text books. By examining the relevant laws and provisions, further discussion on how the conflict of universalism and cultural relativism affect the legality of the whaling.